PERANAN COMPLAINT HANDLING DAN SERVICE RECOVERY OLEH CUSTOMER SERVICE (CS) DALAM RANGKA MENINGKATKAN KEPUASAN DAN LOYALITAS NASABAH PADA PT BANK CIMB NIAGA (PERSERO) TBK - Frianto Pandia; Hendro Endi Yanto (Politeknik Negeri Jakarta, 2012)
Customer service (CS), as frontliners officers who deal directly with customers, have a great influence in improving customer satisfaction and loyalty. Satisfaction and customer loyalty, one of which can be created if the CS staff can handle the complaint and can give a good recovery service for customers. The purpose of this study was to determine what efforts are made CS officers in improving customer satisfaction and loyalty. Then, the authors wanted to find out service activities Complaint Handling and Service Recovery is performed by the CS and in the end the writer wanted to know what constraints are experienced officers in dealing with customer complaints CS, and by providing service recovery. Then, what solutions are applied to the CS in tackling these obstacles. Early research, beginning with observation to the Bank CIMB Niaga Branch Sunter, in order to see how the CS staff in serving customers, handling customer complaints, and in providing service recovery. Next, researchers will conduct a structured interview regarding service activities Complaint Handling and Recovery Servive committed by CS. Then, researchers will conduct the book study by processing the data obtained and compare them with theories that are supported by this study. Keywords: Complaint, Service Recovery, Loya